Pengaruh Dukungan Sosial Orang Tua terhadap Prestasi Belajar melalui Motivasi Belajar Siswa Sekolah Menengah Atas Se-Kecamatan Bayung Lencir - Dwi Aryati; Amirul Mukminin; Robi Hendra (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the effect of parental social support on the learning achievement of senior high school students in Bayung Lencir District through learning motivation as a mediating variable. This study uses a quantitative approach with a survey method. The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of the SmartPLS application. The results of the study indicate that parental social support has a positive and significant effect on student learning motivation with a total effect value of 0.867, a t-statistics value of 25.935, and a p-value of 0.000 (<0.05). Learning motivation is also proven to have a positive and significant effect on student learning achievement with a total effect value of 0.551, a t-statistics value of 5.442, and a p-value of 0.000 (<0.05). Parental social support has a positive and significant effect on academic achievement through learning motivation as a mediating variable, with an indirect effect of 0.477, a t-statistic of 5.100, and a p-value of 0.000 (<0.05). The total effect is 0.913 with a t-statistic of 41.610, indicating a very strong influence. Learning motivation acts as a partial mediator in the relationship between parental social support and student achievement. Parental social support has not only a direct effect but also an indirect effect through increased learning motivation. Thus, parental social support is a crucial factor in improving the motivation and academic achievement of high school students in Bayung Lencir District.